CORE-IBD: a multidisciplinary international consensus initiative to develop a core outcome set for randomized controlled trials in inflammatory bowel disease - Ma, C; Hanzel, J; Panaccione, R; Sandborn, WJ; D'Haens, GR; Ahuja, V; Atreya, R; Bernstein, CN; Bossuyt, P; Bressler, B; Bryant, RV; Cohen, B; et al. (Elsevier, 2022)
Background & Aims End points to determine the efficacy and safety of medical therapies for Crohn’s disease (CD) and ulcerative colitis (UC) are evolving. Given the heterogeneity in current outcome measures, harmonizing end points in a core outcome set for randomized controlled trials is a priority for drug development in inflammatory bowel disease.